STRATEGI KOMUNIKASI ANTAR PRIBADI ANTARA GURU DAN SISWA DALAM MEMOTIVASI MINAT SISWA BELAJAR BAHASA INGGRIS - Aryawan, I Wayan; Putra Adnyana Manuaba, Ida Bagus (Jurnal Kajian Ilmu Komunikasi, 2021)
English is one of the most influential lessons in the present and future, because English is one of the most commonly used international languages ​​at this time. This study aims to find out how interpersonal communication strategies between teachers and students in motivating students' interest in learning English. This research uses a qualitative descriptive approach with data collection methods in the form of interview and documentation techniques. The context of interpersonal communication that the teacher has applied in motivating students' interest in learning English is the psychological, relational, situational, environmental and cultural context